Correlation between Entecavir Penetration in Peripheral Blood Mononuclear Cells and HBV DNA Decay during Treatment of HBeAg-Negative Chronic Hepatitis B. Issue 4 (May 2018) - Nicolò, Amedeo De; Boglione, Lucio; Cusato, Jessica; Fatiguso, Giovanna; Favata, Fabio; Allegra, Sarah; Cariti, Giuseppe; Perri, Giovanni Di; D'Avolio, Antonio
Background: Recently, due to its high effectiveness and tolerability, the treatment of chronic hepatitis B with entecavir became a standard practice. However, limited knowledge is currently available about its pharmacokinetic behaviour and intracellular disposition. Recently, our group reported an inverse correlation between entecavir plasma concentrations and the HBV DNA decay at the first and third month of treatment, respectively. In this paper we investigated the penetration of entecavir in peripheral blood mononuclear cells (PBMC) and in plasma, in order to evaluate the relationship between intracellular penetration and response, in a cohort of naive patients with hepatitis B e antigen (HBeAg)-negative CHB. Methods: Thirty-three patients were prospectively enrolled and gave written informed consent: the monitoring of clinical parameters (for example, HBV DNA, hepatitis B surface antigen [HBsAg], alanine aminotransferase) was carried out at the baseline and then monthly. Entecavir intra-PBMC and plasma trough concentrations were measured at 1 month of treatment, through a validated method based on liquid chromatography coupled with tandem mass spectrometry. Results: While plasma entecavir analysis confirmed previous evidence of inverse correlation between drug concentrations and HBV DNA decrease after 3 months of treatment (r=-0.723; P <0.001), this correlation was not significant for intra-PBMC concentrations. When the intracellular disposition ratio (intra-PBMC/plasma concentration ratio) was considered, it showed a direct and significant correlation with HBV DNA decay at the third month (r=0.485; P =0.004). Conclusions: These results suggest that the antiviral activity of entecavir is dependent on its intracellular uptake, thus resulting in lower plasma concentrations in patients who have a marked HBV DNA decrease during treatment.